PENERAPAN AKUNTANSI SEDERHANA PADA USAHA RETAIL RUMAH TANGGA BERBASIS MONEY MANAGER APPS DI KELURAHAN CIKASUNGKA, KABUPATEN TANGERANG - Ani Kusumaningsih; Lia Ira Sahara, Ani Kusumaningsih, Fery Citra Febriyanto, Baharuddin Saga (KUAT : Keuangan Umum dan Akuntansi Terapan, 2020)
In this Community Service (PKM), the partners we are guiding are the people in the Cikasungka Village, Solear District, Tangerang City. Our target is a household retail business, mostly run by housewives. Based on our observations, we can identify several problems faced by partners, including: very minimal knowledge about management, accounting and information technology. This is based on the relatively low level of education of partners. Moreover, current knowledge as millennial children have about systems/applications such as Money Manager Apps. So the purpose of community service is to provide adequate knowledge to household scale retailers about simple accounting so that it can be applied in everyday life. It is hoped that with the knowledge they have, financial governance can be done better, so that cash flow runs properly and does not cause "losses" (due to mismanagement) in entrepreneurship. The Implementation Method used in carrying out this activity consists of 2 stages: preparation of training and training materials, guidance also assistance.  Keywords: Accounting, Retail Business, Household, Money Manager Apps